2012
DOI: 10.1038/ncomms2313
|View full text |Cite
|
Sign up to set email alerts
|

DJ-1 promotes angiogenesis and osteogenesis by activating FGF receptor-1 signaling

Abstract: Communication between osteoblasts and endothelial cells is essential for bone fracture repair, but the molecular identities of such communicating factors are not well defined. Here we identify DJ-1 as a novel mediator of the cross-talk between osteoblasts and endothelial cells through an unbiased screening of molecules secreted from human mesenchymal stem cells during osteogenesis. We show that DJ-1 stimulates the differentiation of human mesenchymal stem cells to osteoblasts and that DJ-1 induces angiogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 53 publications
2
54
0
Order By: Relevance
“…DJ-1 (PARK7), which was identified as an angiogenic factor secreted from human MSCs, can activate FGFR1-mediated signaling and stimulates both angiogenesis and osteoblast differentiation in vitro. Consistent with these findings, DJ-1 enhances the healing of experimental lesions in a rat model (Kim et al, 2012). Fgf9 heterozygous mutant mice show impaired bone healing, reduced expression of VEGF and VEGFR2 in the lesion, reduced osteoclast recruitment to the callus, and lower MMP9 expression.…”
Section: Angiogenesis In Bone Repairsupporting
confidence: 71%
“…DJ-1 (PARK7), which was identified as an angiogenic factor secreted from human MSCs, can activate FGFR1-mediated signaling and stimulates both angiogenesis and osteoblast differentiation in vitro. Consistent with these findings, DJ-1 enhances the healing of experimental lesions in a rat model (Kim et al, 2012). Fgf9 heterozygous mutant mice show impaired bone healing, reduced expression of VEGF and VEGFR2 in the lesion, reduced osteoclast recruitment to the callus, and lower MMP9 expression.…”
Section: Angiogenesis In Bone Repairsupporting
confidence: 71%
“…Kim et al identified DJ-1 as an angiogenic factor produced by human MSC [40], which induces a direct angiogenic response in EC through activation of FGFR1 and regulates angiogenesis indirectly by stimulating VEGF production by osteoblasts. In addition, DJ-1 stimulates the differentiation of MSC and exogenous administration of DJ-1 enhances bone regeneration in a rodent model of bone fracture repair.…”
Section: Novel Insights In the Stimulation Of Angiogenesis During Bonmentioning
confidence: 99%
“…For example, PARK7 secreted from osteoblasts has been found to promote angiogenesis and osteogenesis [32]. Extracellular deposition of abnormal TTR (transthyretin) protein has been shown to cause familial amyloid polyneuropathy, and secreted PARK7 has been shown to degrade aggregated TTR to protect against the onset of amyloid polyneuropathy [26].…”
Section: Discussionmentioning
confidence: 99%
“…There have been conflicting reports of both increase [28] and decrease [29] in the amount of PARK7 in cerebrospinal fluid in sporadic PD patients as compared with control groups. Secreted PARK7 plays important physiological and pathophysiological roles which include involvement in anti-oxidative effects [30], extracellular signaling between neighboring neuronal cells [31], angiogenic and osteogenic factors [32], and degradation of aggregated protein [26]. Such findings indicate that PARK7 secretion may be implicated in the etiology and/or progression of diseases such as PD and cancer, possibly making it suitable for use as a biomarker.…”
Section: Introductionmentioning
confidence: 99%